Feminist IR in Europe Knowledge Production in Academic Institutions - Stern, Maria; Towns, Ann E. (Trends in European IR Theory,, 2022)
The aim of this open access book is to take stock of, critically engage, and celebrate feminist IR scholarship produced in Europe. Organized thematically, the volume highlights a wealth of excellent scholarship, while also focusing on the politics of location and the international political economy of feminist knowledge production. Who are some of the central feminist scholars located in Europe? How might the concentration of these scholars in Northern Europe and the UK shape the contents of their scholarship? What have some of the main contributions been, in the study of the following themes: security; war and military; peace; migration; international political economy and development; foreign policy; diplomacy; and global governance and international organizations? The volume offers both an intellectual history and a sociology of feminist IR scholarship in Europe. It showcases the vitality and breadth of feminist IR traditions, while simultaneously calling attention to theirpartial nature, exclusions and silences. Maria Stern is Professor in Peace and Development Studies at the School of Global Studies (SGS), Gothenburg University, Sweden. Ann Towns is Professor in Political Science at the University of Gothenburg, Sweden, Director of the GenDip program on Gender and Diplomacy, and a Wallenberg Academy Fellow.